Vaccination for children- when parents doubts are a challenge for doctors - Maria Trojanowska-Szostek; Beata Kulik-Rechberger (Kazimierz Wielki University, 2018)
Most doctors strongly believe that vaccinations are one of the greatest goods in medicine. Obviously, vaccination is a procedure which, results like no other in a decrease in mortality. Vaccinations have significantly reduced the incidence of the infectious disease and even some of them, such as smallpox and polio, have been almost completely eliminated. The widespread implementation of vaccinations considerably improved the individual's health, regardless of gender and age. A question arises why every year a growing number of parents is choosing not to vaccinate their children, despite the obvious benefits from the procedure?